Identification of the Campanian Ignimbrite in the Dead Sea and consequent time-transgressive hydroclimatic shifts in the Eastern Mediterranean - Kearney, Rebecca J.; Schwab, Markus J.; Redant, Daniel; Neugebauer, Ina; Appelt, Oona; Blanchet, Cecile; Fietzke, Jan; Günter, Christina; Müller, Daniela; Tjallingii, Rik; Brauer, Achim (Scientific reports, 2024)
Robust chronologies and time equivalent tephra markers are essential to better understand spatial palaeoenvironmental response to past abrupt climatic changes. Identification of well-dated and widely dispersed volcanic ash by tephra and cryptotephra (microscopic volcanic ash) provides time synchronous tie-points and strongly reduces chronological uncertainties. Here, we present the major, minor and trace element analyses of cryptotephra shards in the Dead Sea Deep Drilling sedimentary record (DSDDP 5017-1A) matching the Campanian Ignimbrite (CI). This geochemical identification expands the known dispersal range of the CI to the southeastern Mediterranean, over 2300 km from the volcanic source. Due to the CI eruption occurring near-synchronous with North Atlantic ice surge of Heinrich Event 4 (HE4), this tephra provides insights into regional responses to large-scale climatic change in the Mediterranean. In the Dead Sea, the CI layer is associated with wetter climatic conditions. This contrasts with the contemporaneous occurrence of the CI deposition and dry conditions in the central and eastern Mediterranean suggesting a possible climate time-transgressive expansion of HE4. Our finding underscores the temporal and spatial complexity of regional climate responses and emphasises the importance of tephra as a time marker for studying large-scale climatic changes verses regional variations.
Gesehen am 23.01.2025